Implicit processes enhance cognitive abilities in mild cognitive impairment. Issue 2 (4th March 2023) - Rowe, Gillian; Troyer, Angela K.; Murphy, Kelly J.; Biss, Renee; Hasher, Lynn
ABSTRACT: Previous work has shown that older adults with typical age-related memory changes (i.e., without cognitive impairment) pick up irrelevant information implicitly, and unknowingly use that information when it becomes relevant to a later task. Here, we address the possibility that implicit processes play a similarly beneficial role in the cognitive abilities of individuals with amnestic mild cognitive impairment (aMCI). Twenty-two individuals with aMCI and 22 matched controls participated in a picture judgment task while instructed to ignore distractions in the form of word/non-word letter strings. Memory for the distracting words was later tested with a word-fragment completion task. Both groups showed a priming effect, that is, they were significantly more likely to solve fragments of previously presented than non-presented words. However, the aMCI group had significantly higher scores than the older adults without cognitive impairment, t (42) = 2.16, p < .05, Cohen's d = 0.67. Our findings suggest that individuals with aMCI can enhance their performance on an explicit cognitive task, in this case, word-fragment completion, if previously exposed to the relevant information implicitly, opening up possible interventions aimed at this population.